MODERNISM AND THE FUNCTIONAL CITY: URBAN RENEWAL IN HAMILTON, ONTARIO AND BUFFALO, NEW YORK (1949-1974) - Rockwell, Margaret T. (My University, 2013)
This dissertation examines urban renewal programs carried out in Hamilton, Ontario and Buffalo, New York, from 1949 to 1974. It shows how these projects fit within the Congrès internationaux d’architecture moderne’s Functional City paradigm and how the modernist aesthetic was reflected in these industrial cities’ planning documents and practices. Urban renewal is often examined by focusing on issues of race, politics and social upheaval. This cross-border study offers a new approach to the analysis through the modernist aesthetic. The comparative study demonstrates that modernist ideas were integral to both Hamilton’s and Buffalo’s urban renewal schemes, contributing both to the desired outcome and to the process, a commitment to action through the destruction of blocks of homes and buildings. The analysis shows how the aesthetic transcended national differences in politics and programs and offers new insight to our understanding of urban renewal on both sides of the international border.
Keywords: urban renewal; modernism; Buffalo; Hamilton; planning; CIAM; History; History